2020
DOI: 10.3390/plants10010018
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Community Composition of Root Associated Endophytic Fungi and Carbon and Nitrogen Stable Isotope Abundance in Two Bletilla Species (Orchidaceae)

Abstract: Mycorrhizae are an important energy source for orchids that may replace or supplement photosynthesis. Most mature orchids rely on mycorrhizae throughout their life cycles. However, little is known about temporal variation in root endophytic fungal diversity and their trophic functions throughout whole growth periods of the orchids. In this study, the community composition of root endophytic fungi and trophic relationships between root endophytic fungi and orchids were investigated in Bletilla striata and B. oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…At a finer time scale, Oja et al (2015) confirmed the turnover of OMF colonizing the roots of N. ovata to be 1 month and that their richness increases at the beginning of the flowering period. Interestingly, the diversity and richness of the detected total fungi tended to show a similar trend, and the flowering period was often accompanied by a significant enrichment of 15 N (Herrera-Rus et al, 2020;Zeng et al, 2021). One of the explanations for the high diversity of fungal partners at flowering period could be host orchids recruit a large number of fungal assemblages that can supplement the nutrients consumed by blooming by releasing specific signals, and that they may even be crucial to the successful completion of the pollination process.…”
Section: Temporal Variation Patternsmentioning
confidence: 95%
“…At a finer time scale, Oja et al (2015) confirmed the turnover of OMF colonizing the roots of N. ovata to be 1 month and that their richness increases at the beginning of the flowering period. Interestingly, the diversity and richness of the detected total fungi tended to show a similar trend, and the flowering period was often accompanied by a significant enrichment of 15 N (Herrera-Rus et al, 2020;Zeng et al, 2021). One of the explanations for the high diversity of fungal partners at flowering period could be host orchids recruit a large number of fungal assemblages that can supplement the nutrients consumed by blooming by releasing specific signals, and that they may even be crucial to the successful completion of the pollination process.…”
Section: Temporal Variation Patternsmentioning
confidence: 95%
“…This indicates that the endophytes have occupied more ecological niches in the aging roots when mycorrhizal activities decreased. One recent study also found that species of Bletilla have higher fungal richness from March to May, when the plants have high physiological activity [51]. In some root-persistent perennial orchids (such as Neottia ovata), the fungal richness is not significantly affected by time and aboveground phenological variations [25].…”
Section: The Scenarios Of Mycorrhizal and Endophytic Fungal Temporal Turnover Of P Bulbocodioidesmentioning
confidence: 93%
“…The fungal community of N. ovata and Bletilla spp. change significantly over time, but those of Corallorhiza maculata, Paphiopedilum spicerianum, and Cypripedium calceolus are not sensitive to seasonal changes [23,25,51,55]. Since fungal migrations across old and young tissues are more difficult in orchids with annual roots, they are inclined to recruit fungi from the soil species pool and thus have more frequent fungal changes [8,24,25,56,57].…”
Section: The Relative Constant Omf Assemblages In P Bulbocodioidesmentioning
confidence: 99%
“…It is worth noting that the composition of orchid microhabitat fungal communities, including endophytic fungi, is unstable and can change seasonally or interannually [20,21]. Only a few studies have considered the seasonal dynamics of fungal colonization and community composition in adult orchid roots [22,23]. For example, Tulasnella were found more frequently as orchid mycorrhizal fungi in the summer, and Leohumicola sp.…”
Section: Introductionmentioning
confidence: 99%